FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Olga Theolina Sitorus (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
The aims of this study is to analyze factors influence stock return consist of earningsper share, earning management, investment opportunity set, risk (beta), companies size,leverage and sales price ratio.Population of this research are go public manufacturing companies which enlist atIndonesia Stock Exchange from 2006-2009 and samples are taken by purposive samplingmethod, that is taking samples by some criteria. Sample that used in this research are 36manufacturing companies listed in the Indonesia Stock Exchange from 2006-2009 withamount 144 observation . The using of analyze method is by multiple linier regression.Hypothesis testing using the t test and F test.The result of this research show by simultan that earnings per share, earningmanagement, investment opportunity set , risk (beta), companies size, leverage, and sales priceratio have an effect on stock return at firms listed in Indonesia Stock Exchange of perceptionperiod 2006-2009. While by Partial show that earnings per share have no influence significantto stock return, earning management have positive significant influence to stock return ,investment opportunity set have positive influence significant to stock return, risk (beta) havepositive influence significant to stock return, companies size have no influence significant tostock return, leverage have positive influence significant to stock return and sales price ratiohave no influence significant to stock return.Keywords: earnings per share, earning management, investment opportunity set, risk (beta),companies size, leverage, sales price ratio, stock return